Geochemistry of basalt lavas from Vestfjella and adjacent areas, Dronning Maud Land, Antarctica - Furnes, Harald; Vad, Erik; Austrheim, Håkon; Mitchell, John G.; Garmann, Leif B. (Lithos, 1987)
K-Ar ages, major- and trace-element compositions, and Sr-isotope data are presented for basalt lavas from Vestfjella, Dronning Maud Land, Antarctica. The new conventional K-Ar age data have yielded ages from 171 ± 2 to 695 ± 11 Ma, but the youngest (i.e. Middle Jurassic) ages are preferred. Mineralogical and chemical data show that the majority of the basalts are tholeiites. Petrographic mixing calculations, REE modelling, and the Sr isotope data suggest that they were derived by partial melting of garnet-free lherzolites with variable REE patterns, and subsequently modified by fractionation of olivine, Ca-rich pyroxene and plagioclase. Incompatible trace-element data from nearby Middle Jurassic basalt lavas (from Kirwanryggen and Heimefrontfjella) suggest a different source and REE modelling indicates generation from garnet lherzolites.
Keywords: Dronning Maud Land; NARE 1976/77; geokjemi; geologi; mineralogi; paleontologi; petrografi

Nye fossile virveldyr fra Antarktis - Heintz, Natascha (Naturen, 1982)
Keywords: Antarktis; fossiler; paleontologi

Fossile virveldyr fra Antarktis - Heintz, Natascha (Naturen, 1972)
Keywords: Antarktis; paleontologi